PERENCANAAN DAN PENGORGANISASIAN SEKOLAH UNGGUL BERBASIS SOFT SKILLS - Warsiman Warsiman; Karyanto Karyanto; Endang Sulistiyorini (IKIP PGRI Bojonegoro, 2022)
Abstract: The purpose of this study was to determine the planning and organization of soft skills-based superior school programs at SMAN 1 Sidoarjo. The method used is a descriptive method with a qualitative approach. The subjects of this research include principals, teachers, education staff, students, and all those involved in the program. The research instruments are interviews, observations, and documentation. The findings data were analyzed and presented in a qualitative descriptive manner. The results showed that the implementation of a superior school based on soft skills at SMAN 1 Sidoarjo required careful planning and good organization. Planning activities start from equalizing a common determination in running the program, adjusting the program to the school's vision and mission, involving all stakeholders, identifying potentials, identifying soft skills values that will be developed, and socializing to all school members. Meanwhile, organizing activities begin with structuring the main tasks and functions, division of work responsibilities, setting priorities for school readiness, supporting funding sources, financial transparency, and providing facilities and infrastructure that can support the program. The conclusion is that planning and organizing superior schools based on soft skills is absolutely necessary to ensure the implementation of the program. Keywords: Planning, organizing, superior school, soft skills. Abstrak: Tujuan penelitian ini adalah untuk mengetahui perencanaan dan pengorganisasian program sekolah unggul berbasis soft skills di SMAN 1 Sidoarjo. Metode yang digunakan adalah metode deskriptif dengan pendekatan kualitatif. Subyek penelitian ini meliputi kepala sekolah, guru, tenaga kependidikan, siswa, dan semua yang terlibat dalam program. Instrumen penelitian ini ialah wawancara, observasi, dan dokumentasi. Data temuan dianalisis dan dipaparkan secara deskriptif kualitatif. Hasil penelitian menunjukkan bahwa implementasi sekolah unggul berbasis soft skills SMAN 1 Sidoarjo diperlukan perencanaan yang matang dan pengorganisasian yang baik. Kegiatan perencanaan dimulai dari menyamakan tekad bersama dalam menjalankan program, menyesuaikan program dengan visi dan misi sekolah, melibatkan seluruh stakeholder, identifikasi potensi, identifikasi nilai-nilai soft skills yang akan dikembangkan, dan sosialisasi kepada seluruh warga sekolah. Sedangkan kegiatan pengorganisasian diawali dari penataan tupoksi (tugas pokok dan fungsi), pembagian tanggung-jawab kerja, penetapan prioritas kesiapan sekolah, dukungan sumber dana, keterbukaan finansial, dan penyediaan sarana dan prasarana yang mampu mendukung program. Kesimpulannya adalah perencanaan dan pengorganisasian sekolah unggul berbasis soft skills mutlak diperlukan untuk menjamin terlaksanannya implementasi program. Kata Kunci: Perencanaan, pengorganisasian, sekolah unggul, soft skills.